The Incidence of Hyperthermia during Craniotomy. Issue 4 (July 2018) - Malpas, G.; Taylor, J. A.; Cumin, D.; Merry, A. F.; Mitchell, S. J.
There is evidence that even mild hyperthermia may exacerbate brain injury. There seem reasonable grounds for considering patients undergoing craniotomy as 'at risk' for brain injury. A retrospective observational study was undertaken to measure the incidence of mild hyperthermia in craniotomy cases in which the patient was initially normothermic. Auckland City Hospital's database of electronic anaesthetic records was searched for adult patients who were normothermic (≤37°C) prior to undergoing craniotomy procedures. For each case, demographic data, intraoperative naso- or oropharyngeal temperature measurements, and paracetamol use were extracted. We identified the proportion of patients whose temperature rose to exceed normal (>37°C) and further subdivided that group into the proportion in whom the temperature rose to ≥38°C. Two thousand, nine hundred and thirty-five craniotomy cases began their operations while normothermic and had adequate temperature data collected. There were 984 (33.5%) cases that had at least one temperature reading >37°C, for a mean (standard deviation [SD]) time of 66.0 (64.6) minutes, and 49 (1.7%) cases that had at least one reading ≥38°C for a mean (SD) time of 40.4 (38.1) minutes. The majority (77.8%) who became mildly hyperthermic remained so at the end of the procedure. New mild hyperthermia occurs commonly during craniotomy. In view of the compelling evidence of potential harm arising from mild hyperthermia in brain injury, these findings suggest an opportunity for practice improvement in the anaesthetic management of craniotomy patients. Reasonable steps should be taken by anaesthetists to avoid intraoperative hyperthermia of any degree.